ADOLESCENT ATTITUDES ABOUT SEXUALLY TRANSMITTED DISEASES WITH PREMARITAL SEX RESPOND IN MANDIRI PRIVATE VOCATIONAL SCHOOL, JOMBANG REGION - siti mudrikatin; Asef Wildan Munfadlila (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2020)
Abstract Introduction: Attitude is the reaction or response of someone who is still closed to the stimulus or object. Sexually transmitted infections are diseases that can be transmitted from one person to another through sexual contact. Premarital adolescent sexual intercourse is sexual intercourse carried out by adolescents before marriage. This study is to understand the relationship of adolescents about sexually transmitted infections with premarital sex in the Independent Practice of the Jombang Regional Midwife in 2019. Method: The research method used is correlational analytic with cross sectional research, that is, research that requires measurement / observation time, variable, free and variable data, which is collected simultaneously at a certain time, so it does not need to be continued. The population of young women in the Independent Practice of the Jombang Regional Midwife is 92 people. The sample of this study was 75 people. Results: The results of this study are Adolescent attitudes about infectious infections more than half of 45 respondents (60%) with positive attitudes and attitudes about premarital sex more than half 45 respondents (62.7%) with positive attitudes. Conclusion: The results of the analysis using the Chi-Square statistical test, obtained the probability number (p) = 0,000 <(α = 0.05), then H0 is rejected and H1 is accepted, meaning that there is a relationship with women about the protection of sexually transmitted sex with premarital sex in Independent Practice of the Jombang Regional Midwife in 2019. Efforts should be made to overcome the problems of open sharing or consultation of related issues or protected matters in the BK (Counseling Guidance) and also as midwives their knowledge of premarital sex should be increased Keywords: attitude, sexually transmitted infections, premarital sex